Evaluation of Care Processes and Health Care Utilization in Newly Implemented Medical Homes in Italy: A Population-Based Cross-sectional Study. (May 2020) - Alcusky, Matthew; Singer, David; Keith, Scott W.; Hegarty, Sarah E.; Lombardi, Marco; Saccenti, Elena; Maio, Vittorio
In the Local Health Authority (LHA) of Parma, Emilia Romagna, Italy, 16 medical homes were established between 2011 and 2014. The authors implemented a 1-year (January 1, 2015, to December 31, 2015) cross-sectional population-based design to compare utilization and processes of care between medical homes and comparison practices using the Parma LHA administrative health care database. Residents (n = 372 396) attributed to a primary care physician practicing in a medical home as of January 1, 2015, were considered exposed to medical homes. Adjusted rates of emergency department (ED) use (incidence rate ratio [IRR] = 0.86; 95% CI = 0.82-0.90), potentially avoidable ED use (IRR = 0.78; 95% CI = 0.72-0.84), and hospitalization for chronic ambulatory care sensitive conditions (ACSCs; IRR = 0.87, 95% CI = 0.78-0.97) were lower among patients in medical homes. Performance on process of care measures favored the medical home group; however, associations were generally weak. Receipt of care in medical homes in Parma LHA was associated with lower rates of avoidable ED visits and hospitalizations for chronic ACSCs.